Atazanavir and chest pain. (May 2014) - Phillips, Matthew; Saxon, Cara; Lee, Vincent
We present a case of a 41-year-old man complaining of chest pain, which he directly attributed to his antiretrovirals, specifically atazanavir and ritonavir. The chest pain resolved on stopping the treatment, and recurred when atazanavir was restarted, again resolving on discontinuation. Cardiovascular risk factors are an important consideration with any antiretroviral therapy but particularly with protease inhibitors. The association between atazanavir and cardiac arrhythmias has been reported elsewhere including the British National Formulary, and it may be good practice to perform electrocardiogram assessments in patients commencing and using atazanavir-based regimens.